Engenharia da sustentabilidade: análise da eficiência do controle secundário de tensão aplicado em um parque eólico - PINHEIRO NETO, Sérgio Rodrigues (2022)
This final paper presents the contribution of secondary voltage control (SVC) applied to a wind farm composed of doubly fed induction generator (DFIG) and its effect on long-term voltage stability in order to show the feasibility of voltage safety systems and their acquisitions in the context of sustainability engineering and eco-efficient production. Variable speed wind turbines are capable of providing reactive power thanks to the power converters, which are subject to voltage and current limitations, and depend on the operating conditions of the power system and the wind regime. With the increase of the electric power generated by wind farms, some challenges related to voltage stability arise due to the variability and uncertainty of the wind. Safety and operational measures are necessary to solve any problems related to the control of voltage stability, such as the SVC. Power factor control, voltage control and reactive power control refer to the capacity of the wind farm to provide reactive power to the power grid in order to improve the voltage stability of the power system. Considering a power system commonly used in voltage stability studies with the insertion of a wind farm, simulations were performed in computer software used in power system analysis studies developed by the Electric Energy Research Center (CEPEL). The results showed that SVC is effective when applied to DFIG in increasing the long-term voltage stability margin, improving your energy efficiency and improving your eco-efficiency.